2022
DOI: 10.1111/dth.15685
|View full text |Cite
|
Sign up to set email alerts
|

The role of lifestyle and nutrition in psoriasis: Current status of knowledge and interventions

Abstract: Extrinsic environmental factors, including patient lifestyle (alcohol intake, smoking, stress, sleep disturbances, and sedentary habit), diet and single nutrients intake may affect psoriasis clinical presentation, severity, and course. All English language articles dealing with psoriasis and lifestyle factors or diet gathered by an extensive PubMed search were carefully examined in order to explore their impact on the disease. Current authoritative knowledge confirms that low-calories, Mediterranean, and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Further, a meta‐analysis of 18 RCTs involving 927 study participants in 2020 found that fish oil or omega‐3 PUFAs monotherapy had little effect on psoriasis area and severity indices; however, they could show significant adjunctive effects when combined with traditional treatments (Chen et al, 2020 ). A review suggested that eating fish rich in n‐3 PUFAs, as well as fruits and vegetables, are beneficial for people with psoriasis (Musumeci et al, 2022 ). Some researchers have pointed out that the roles of n‐3 and n‐6 PUFAs in most common skin diseases are opposite and uncertain, but they are not simply black and white.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a meta‐analysis of 18 RCTs involving 927 study participants in 2020 found that fish oil or omega‐3 PUFAs monotherapy had little effect on psoriasis area and severity indices; however, they could show significant adjunctive effects when combined with traditional treatments (Chen et al, 2020 ). A review suggested that eating fish rich in n‐3 PUFAs, as well as fruits and vegetables, are beneficial for people with psoriasis (Musumeci et al, 2022 ). Some researchers have pointed out that the roles of n‐3 and n‐6 PUFAs in most common skin diseases are opposite and uncertain, but they are not simply black and white.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake is related to psoriasis severity whereby a diet high in saturated fat and red and simple sugar is associated with inflammation. Meanwhile, vitamin D, vitamin B12, vitamin A and selenium play an important role in improving severity [ 6 , 103 , 104 ]. Therefore, dietary assessment is pertinent to determine the nutritional status of patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with psoriasis who are overweight and obese are more likely to develop MetS. Therefore, early dietary intervention is needed to improve the nutritional status, reduce the risk of metabolic disorders and improve the effectiveness of treatments [ 103 , 104 , 109 , 110 ]. Dietary recommendations are often individualised based on the patients’ comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the premise of a vegetarian diet is to eschew meat and meat products in favour of large amounts of groats, cereals, legumes, vegetables, fruits, nuts, and mushrooms, reduces the supply of arachidonic acid and its derivatives, prostaglandins and leukotriene B4, which have pro-inflammatory effects [66]. A vegetarian diet benefits weight maintenance, as it results in a lower intake of saturated fatty acids and cholesterol, which is important for patients with psoriasis.…”
Section: Vegetarian Dietmentioning
confidence: 99%